COMMITMENT-BASED HR PRACTICES AND THEIR IMPACT ON JOB IMMERSION: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF FACULTY MEMBERS IN PRIVATE UNIVERSITIES AND COLLEGES OPERATING IN THE HOLY CITY OF KARBALA AND BABIL (World Bulletin of Social Sciences, 2023)
The current research seeks to determine the nature of the influence relationships and the correlation between human resource practices based on commitment in job immersion at the level of private universities and colleges in the holy city of Karbala. Functional immersion through three dimensions (cognitive immersion, emotional immersion, behavioral immersion). The analytical descriptive approach was relied upon in presenting the research topics. The questionnaire was also used as a main tool in collecting data and information. The sample consisted of (205) faculty members. A set of statistical methods and tools were used in analyzing the data, represented by the normal distribution test, confirmatory factor analysis, descriptive statistics, Pearson correlation analysis, and structural equation modeling. These methods were used on statistical programs (SPSS V.25, Amos V.25) The research reached a number of conclusions, the most important of which are: Human resources based on commitment through faculty members and attention to their entitlements would enhance their performance and their superiority over competitors, and the research concluded with a number of .appropriate recommendations